The Effects of Islamic Financing, Islamic Financial Literacy, and Digital Marketing on MSME Growth - Wita Khamala Putri; Rafidah; Anzu Elvia Zahara (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study aims to analyze the factors that affect the growth of Micro, Small, and Medium Enterprises (MSMEs) in Jambi City. The study focuses on three main factors: Islamic financing, Islamic financial literacy, and digital marketing. A quantitative research method was used with 100 MSME owners as respondents. The sample was selected using the Slovin formula and purposive sampling technique. Primary data were collected through a questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results show that Islamic financing has a positive and significant effect on MSME growth. Islamic financial literacy also has a positive and significant effect on business growth. In addition, digital marketing significantly supports the growth of MSMEs. These findings indicate that access to Islamic financing, a good understanding of Islamic financial literacy, and the use of digital marketing are important factors for sustainable MSME growth. This study provides useful information for policymakers and Islamic financial institutions to improve financial education and provide better digital support for MSMEs.